Implementasi Model STAD pada Pembelajaran Penanganan Limbah guna Meningkatkan Partisipasi dan Hasil Belajar Siswa - Tokhibin, Tokhibin (Paedagogie, 2019)
The present research aimed at enhancing students’ participation and achievement in waste handling. This Classroom Action Research was conducted through two cycles, started from planning, action, observation and reflection. STAD was implemented in the learning process divided into four phases, namely presentation, discussion, quiz, and group reward. Data of students’ participation were gathered through questionnaire and observation, while the achievement was gathered through tests. The results revealed that improvement of the variables from Pre-Cycle, Cycle I to Cycle II existed. Students’ participation enhanced from 42,3 % to 78.74%. So did the students’ achievement from 71, 75 to 81. Hence, the implementation of STAD Model could enhance students’ participation and achievement in waste handling.